MENUJU PENDIDIKAN ACEH YANG BERBASIS ENTREPRENEURSHIP - M. Shabri A. Majid (Majelis Pendidikan Daerah (MPD) Aceh dan Universitas Syiah Kuala, 2015)
This article is aimed at discussing descriptively the important role of educational institution in Aceh in producing the entrepreneurial-minded graduates. Limitations of jobs available for graduates of educational institutions, especially in Aceh require educational institutions to be able to produce the graduates who can create employment opportunities, rather than seize the existing jobs offered by the government and private agencies. A formal and an informal entrepreneurship-based education are believed to be able to offer alternative solutions to create job oppotunities, and in turns will solve economic problems of Aceh by boosting economic growth and enhancing welfare of the people of Aceh. In order to create the entrepreneurship education become more effective and be able to produce young entrepreneurs in Aceh, the educational institutions there should reformulate curriculum-based entrepreneurship, enhance the cooperation and partnerships with the private sector, and attract more supports from the government and public sector. The quality, skills, and experiances of the entrepreneurial teachers/tutors must also be countiously improved